If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = x + 5x + 4 Reorder the terms: -10 = 4 + x + 5x Combine like terms: x + 5x = 6x -10 = 4 + 6x Solving -10 = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -10 + -6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 + -6x = 4 + 0 -10 + -6x = 4 Add '10' to each side of the equation. -10 + 10 + -6x = 4 + 10 Combine like terms: -10 + 10 = 0 0 + -6x = 4 + 10 -6x = 4 + 10 Combine like terms: 4 + 10 = 14 -6x = 14 Divide each side by '-6'. x = -2.333333333 Simplifying x = -2.333333333
| g-10+7g=25+3g | | 120/x=-3x | | (x^2-6)(x-3i)=0 | | -2x-3y=-3 | | 7=2(p-3) | | y=-3(9)+4 | | 8x+4x+3+6=3x+3+8x | | 2/3t-3=1 | | 6n^2-7n-5=0 | | -7x+5=x^2-11x-7 | | 82-5x=22 | | 7+2x+7x=-65 | | (125x^10)^-1/6 | | -2(2b+3)+(5b-9)=0 | | 2n-7=3n-3 | | 5x+7-3(x+1)=9x+6 | | 5(x)-12=53 | | 13(-12)+10+x=11 | | 8-4y=5 | | 2sinx-2=0 | | h^2+3h-29=0 | | 265=25x+39.0625 | | z/14=3 | | 15x=10+10x | | 16(v+4)-4v=4(3v+3)-14 | | x+(31+x)+(-37+3*x)=569 | | 13-12+10+x=11 | | -4(-15)/14-(-6) | | Y=40+0.80 | | 3x^2-11x=8-14 | | 40+0.80y= | | 40+0.8= |